SISTEM INFORMASI RANCANGAN ANGGARAN BIAYA PADA PT. BUKAKA TEKNIK UTAMA PLTA MAMUJU - Haerunnisa, Dian Aprilia; Endang, Andi Hutami; Paramita, Andi Jamiati (Jurnal INSYPRO (Information System and Processing), 2024)
Access and processing of data and information are essential for an organization. The processing should be computerized using an information system to facilitate the organization. PT. Bukaka Teknik Utama is a company engaged in construction and manufacturing. This study aims to design an information system for PT. Bukaka Teknik Utama's Mamuju Hydropower Project to digitally submit and approve the bridge project's budget. The research began with observation, followed by a literature study from various sources, including books and the Internet. Subsequently, the researcher conducted direct interviews at PT. Bukaka regarding the budget format. The research was conducted over 12 months. The type of research carried out is applied research. The application design uses Laravel and ReactJs. The methods used in this study are waterfall and Blackbox for system testing. The results of the study show success with the designed system